Functions of Code-Switching in Tweets: An Annotation Scheme and Some Initial Experiments - Begum, Rafiya; Bali, Kalika; Choudhury, Monojit; Rudra, Koustav; Ganguly, Niloy (LREC, 2016)
Code-Switching (CS) is very common among multilinguals who switch between two or more languages when communicating or having a dialogue with each other. People have not constrained CS to just spoken form but also have introduced this concept to written text. Due to the popularity of social-media, people have used this platform to perform CS in the text form. This gave rise to the need of computational processing of the code-switched data. In this study, we focus on CS between English and Hindi in the Twitter corpus which is an informal text. With the help of this data, we have done a detailed linguistic study of various aspects of CS. For understanding, processing, and generation of code-switched data, we need annotated code-switched data. Hence, in this paper, we present an annotation scheme for annotating the functions of CS in Hindi-English (Hi-En) code-switched tweets and we also present some initial experiments. In this effort, we are focusing on CS in text data from social-media whereas earlier studies have focused on CS in spoken data from a small number of speakers.